Fault Zone Imaging With Distributed Acoustic Sensing: Body‐To‐Surface Wave Scattering. Issue 11 (17th November 2022) - Atterholt, James; Zhan, Zhongwen; Yang, Yan
Abstract: Fault zone structures at many scales largely dictate earthquake ruptures and are controlled by the geologic setting and slip history. Characterizations of these structures at diverse scales inform better understandings of earthquake hazards and earthquake phenomenology. However, characterizing fault zones at sub‐kilometer scales has historically been challenging, and these challenges are exacerbated in urban areas, where locating and characterizing faults is critical for hazard assessment. We present a new procedure for characterizing fault zones at sub‐kilometer scales using distributed acoustic sensing (DAS). This technique involves the backprojection of the DAS‐measured scattered wavefield generated by natural earthquakes. This framework provides a measure of the strength of scattering along a DAS array and thus constrains the positions and properties of local scatterers. The high spatial sampling of DAS arrays makes possible the resolution of these scatterers at the scale of tens of meters over distances of kilometers. We test this methodology using a DAS array in Ridgecrest, CA which recorded much of the 2019 Mw 7.1 Ridgecrest earthquake aftershock sequence. We show that peaks in scattering along the DAS array are spatially correlated with mapped faults in the region and that the strength of scattering is frequency‐dependent. We present a model of these scatterers as shallow, low‐velocity zones that is consistent with how we may expect faults to perturb the local velocity structure. We show that the fault zone geometry can be constrained by comparing our observations with synthetic tests. Plain Language Summary: Fault zones are multi‐scale structures that govern where and how earthquakes happen. Characterizing fault zones at all scales is thus important for understanding earthquake ruptures and earthquake‐related hazards. However, finding and describing fault zones at small scales remains a persistent challenge in earthquake science. We propose a framework for the characterization of fault zones using distributed acoustic sensing (DAS), a recently developed technique that converts fiber optic cables into dense networks of ground motion sensors. Earthquake waves are scattered when they encounter fault zones, and this scattering creates signatures in DAS data that we can use to locate these fault zones. Additionally, the behavior of fault zone scattered waves with frequency may illuminate detailed characteristics of the fault zone. We test this framework using a DAS network in Ridgecrest, CA that recorded aftershocks of the 2019 magnitude 7.1 Ridgecrest earthquake. We use these recordings to map fault zone locations near the network. These locations are close to previously mapped faults but are more accurate. By comparing the behavior of observed fault zone scattered waves with frequency with that of simulations, we can constrain shallow fault zone geometry. Key Points: We develop a framework for systematically locating fault zones at sub‐kilometer scales using the distributed acoustic sensing‐measured earthquake wavefield We present a model for these fault zones and use simulations to show that this model reproduces first‐order observations of scattering By comparing observations with synthetics, we use this method to constrain local fault zone geometry